An Analysis of the Impact of FPKM Funds on Community Empowerment and Sustainability in Local Economies - Selamet Edi Sucipto; Ardy Adipura; Febrian Chandra (International Journal Of Economics Social And Technology, 2026)
This study aims to explore and analyze the effectiveness of distributing mandatory Community Plantation Facilitation (FPKM) funds on local economic empowerment within the framework of achieving the Sustainable Development Goals (SDGs). The study employs an explanatory literature approach (mixed-method design) that integrates a review of sectoral macroeconomic data with a socio-legal analysis of plantation regulation implementation. The synthesized data reveals that the plantation sector consistently contributes positively to the regional Gross Domestic Product (GDP); however, the multiplier effect on local communities is frequently suboptimal due to the delayed realization of the 20% FPKM mandate. Effective FPKM distribution distinct from mere social assistance or Corporate Social Responsibility (CSR) has proven capable of serving as a long-term productive asset that transforms the rural economy and mitigates inequality, while simultaneously preserving environmental carrying capacity through sustainable palm oil governance practices. The study concludes by emphasizing the necessity for legal harmonization among local governments, corporations, and indigenous communities to ensure the accountability of FPKM profit-sharing as a driving force for green economic instruments. However, the limitations of this study include the reliance on macroeconomic secondary data which may not capture micro-level governance nuances in non-palm oil sectors.